Design of shallow foundations - French, Samuel E. 1930- (ASCE Press, 1999)
"Design of Shallow Foundations presents a complete "how to" procedure for the design of shallow foundations commonly used with low-rise structures of today's building codes. This book offers a detailed presentation of both soils and structures, specifically as they relate to shallow foundations, emphasizing soil-structure interaction by matching particular structural designs to particular soil conditions. For studies related to soils, it includes a treatment of relevant soil properties and soil mechanics at shallow depths; for structures, it includes a summary of loads on foundations and the deformations produced by such loads."--BOOK JACKET.